(2+1)(2 ²+1) ($2^{4}$+1) ($2^{8}+1)($2^{16}+1)

(2+1)(2 ²+1) ($2^{4}$+1) ($2^{8}+1)($2^{16}+1)

2 bình luận về “(2+1)(2 ²+1) ($2^{4}$+1) ($2^{8}+1)($2^{16}+1)”

  1. Giải đáp:
     
    Lời giải và giải thích chi tiết:
    3.(22+1).(24+1).(28+1).(216+1)
    =(22-1).(22+1).(24+1).(28+1).(216+1)
    =(24-1).(24+1).(28+1).(216+1)
    =(28-1).(28+1).(216+1)
    =(216-1).(216+1)
    =232-1

    Trả lời
  2. (2+1)(2^2+1)(2^4+1)(2^8+1)(2^16+1)
    =(2-1)(2+1)(2^2+1)(2^4+1)(2^8+1)(2^16+1)
    =(2^2-1)(2^2+1)(2^4+1)(2^8+1)(2^16+1)
    =(2^4-1)(2^4+1)(2^8+1)(2^16+1)
    =(2^8-1)(2^8+1)(2^16+1)
    =(2^16-1)(2^16+1)
    =2^32-1

    Trả lời

Viết một bình luận

Câu hỏi mới